Modelling and mapping groundwater flooding at the ground surface in Chalk catchments. (21st August 2015) - Morris, S.E.; Cobby, D.; Zaidman, M.; Fisher, K.
Abstract: There are several mapping products available that depict areas susceptible to groundwater flooding; however, they are not comparable in detail to the risk maps developed for fluvial, tidal and surface water flooding that are used by risk management authorities. This paper reports on a new approach to groundwater flood risk mapping for unconfined Chalk aquifers. This approach recognises the synergies between surface water flooding and groundwater flooding once groundwater has emerged at the surface. The volume of groundwater at the surface is modelled by identifying the zone of groundwater emergence and calculating the rate of emergence using a Darcy approach. Flow is then routed using a bespoke two‐dimensional hydraulic model to give the depth and extent of groundwater flooding. These groundwater emergence and routing maps are calibrated on measured groundwater flow and observed flood extents. The maps are anticipated to be used to plan for and manage future groundwater flooding events.